Galectin-1 Used in Assisted Reproduction—Embryo Safety and Toxicology Studies - Roncoletta, Marcelo; de Sales, Nathali Adrielli Agassi [UNESP]; Rey, Fernando Sebastian Baldi [UNESP]; Ferraz, Guilherme Camargo [UNESP]; Morani, Erika da Silva Carvalho (MDPI, 2023)
Galectin-1 has been cited as a mediator involved in preventing early embryonic death in mammals and is implicated in maternal–fetal tolerance. Galectin-1 is also a reasonable tool to improve fertility in assisted reproduction procedures. As recommended in the ICH guidelines (S5-R2 and S6-R1) and based on bioethical concerns, we chose bovine embryos (BE) to assess in vitro embryo development as part of a larger reproductive safety and toxicology study in progress. The design considered in vitro embryo development using rHGAL-1 supplementations (in three different concentrations) of the in vitro embryo culture (IVP) media. Based on procedures for the commercial in vitro production of BE using oocytes aspirated from slaughterhouse ovaries, rHGAL-1 supplementation was performed in two experiments: In Experiment 1 on oocyte maturation, involving IVM medium supplementation, and in Experiment 2 on culture step IVC, involving supplementation with an SOF medium. IVP commercial procedures were used, with three IVP replicates per experiment, and the oocytes we distributed into four groups of treatment (one control group and three different dosages of rHGAL-1 to supplement both IVM and SOF media using 2, 20, and 40 µg·mL−1, respectively. A total of 967 (Experiment 1) and 1213 (Experiment 2) oocytes were aspirated and submitted to the IVP procedure. There was no damage to the in vitro bovine embryo growth when considering cleavage percentage (%CLE), blastocyst development (Bl, Bx, Bh, and B) at Days 7 and 8, or an amount of rHGAL-1 supplementation ≤20 µg·mL−1. The immunohistochemistry assay with D8 embryos cultivated using rHGAL-1 supplementation on the culture medium (SOF medium) demonstrated the presence of exogenous GAL-1 distributed in mass cell and trophoblastic cells, and the profile observed was dependent on exogenous supplementation, which was most evident in hatched embryos. The findings confirmed the use of a reasonable amount of rHGAL-1 for in vitro embryonic development and would make the use of rHGAL-1 in assisted reproduction in humans more reliable and safer. Even though it was not the objective of the study, we verified that supplementation with 2 µg·mL−1 significantly improved some of the evaluated parameters of embryonic development (%BlD7, %BD7, %BlD8, %BhD8, and %BD8).
Keywords: galectin-1; recombinant protein; reproductive safety toxicology; Tolerana®